Lithium ion battery positive electrode material slurry and preparation method thereof, prepared positive electrode and lithium ion battery

By using dearamating solvent oil and rubber as the binder system for the slurry of lithium-ion battery positive electrode material, the problems of environmental pollution, human body hazards and high preparation costs in the prior art are solved, and the preparation of high-performance and environmentally friendly lithium-ion battery positive electrode materials are realized.

CN115395017BActive Publication Date: 2025-03-25GUANGZHOU GREAT POWER ENERGY & TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202211181309.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-27
Publication Date
2025-03-25
Estimated Expiration
2042-09-27

AI Technical Summary

Technical Problem

The existing lithium-ion battery positive electrode material slurry system has problems such as environmental pollution, human body harm, difficulty in controlling humidity, low peeling strength and high preparation cost.

Method used

A high-performance lithium-ion battery positive electrode material slurry is prepared by dissolving the rubber binder in the dearomatic solvent oil and rubber as the binder system.

Benefits of technology

The prepared extreme sheet is smooth and soft, has high peeling strength, excellent battery performance, and the system is environmentally friendly and non-toxic, reducing the preparation cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003865615240000151
    Figure BDA0003865615240000151
  • Figure BDA0003865615240000161
    Figure BDA0003865615240000161
  • Figure BDA0003865615240000171
    Figure BDA0003865615240000171
Patent Text Reader

Abstract

The present invention provides a lithium ion battery positive electrode material slurry and a preparation method thereof, a prepared positive electrode and a lithium ion battery, and relates to the technical field of lithium ion batteries. The lithium ion battery positive electrode material slurry comprises an active substance, a conductive agent, a binder and a solvent. Among them, the solvent is an environmentally friendly and non-toxic dearomatized solvent oil, and the binder is a rubber binder that can be dissolved in the dearomatized solvent oil. Compared with the N-methylpyrrolidone and polyvinylidene fluoride system of the traditional lithium ion positive electrode slurry, the dearomatized solvent oil and rubber binder system of the present invention is more environmentally friendly and pollution-free, the choice of binder is more diverse, and the performance of the prepared battery is also improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium ion battery positive electrode material slurry and a preparation method thereof, and the prepared positive electrode and lithium ion battery. Background Art

[0002] Common positive electrode slurry systems for lithium-ion batteries include N-methylpyrrolidone and polyvinylidene fluoride systems and deionized water and aqueous binder systems. Among them, the N-methylpyrrolidone and polyvinylidene fluoride system is the most commonly used system in the battery industry, but N-methylpyrrolidone has serious pollution and damage effects on the environment and human body; polyvinylidene fluoride is sensitive to moisture, and a trace of moisture can make polyvinylidene fluoride ineffective, so during use, it is necessary to strictly control the humidity of each process; in addition, the pole piece prepared by polyvinylidene fluoride has low peeling strength, and it is necessary to cooperate with various surface-treated current collectors to increase the peeling strength of the pole piece, which greatly increases the preparation cost of the battery. Although the deionized water and aqueous binder system is pollution-free to the environment and harmless to the human body, the slurry prepared using this system is unstable, the pole piece prepared is relatively hard and brittle, and the pole piece scrap rate is extremely high, which is difficult to apply to the normal production process.

[0003] Rubber has good wear resistance, high elasticity, tear strength and elongation, good chemical stability, in addition, it also has water resistance, air tightness and excellent bonding properties. Rubber products are of various types and rich in material sources. Single or multiple rubbers can be selected as the binder system of lithium-ion battery slurry. In the preparation process of lithium-ion battery slurry, organic solvents need to be added to dissolve the rubber binder. Commonly used rubber organic solvents include cyclohexane, benzene, toluene, xylene, trichloroethylene, aromatic hydrocarbons, etc. These organic solvents are relatively toxic and have serious harm to the human body and the environment. Dearomatized solvent oil is a cycloalkane and chain alkane without aromatic hydrocarbons. It has good solubility characteristics for rubber and also meets the standards of safety, health and environmental protection. Using dearomatized solvent oil and rubber as the lithium-ion battery slurry system, the prepared pole piece is smooth and soft, the peel strength of the pole piece is higher than that of N-methylpyrrolidone and polyvinylidene fluoride system, and the battery performance is better.

[0004] In the manufacturing method of the positive electrode sheet of a lithium-iron disulfide battery in CN102779973A, rubber G1651 is used as a binder. The battery in this patent is a disposable lithium-ion battery, which is different from the repeatedly chargeable and dischargeable lithium-ion battery of the present invention. The requirements of the binder for disposable lithium-ion batteries focus on good adhesion between particles, while the requirements of the repeatedly chargeable and dischargeable lithium-ion batteries for binders not only ensure good adhesion between particles, but also ensure good adhesion between particles and positive electrode current collectors, thereby ensuring that the battery has good charge and discharge performance. Therefore, SEBS modified with maleic anhydride is more suitable for repeatedly chargeable and dischargeable lithium-ion batteries.

[0005] Patent CN102779973A and Patent CN102037591A use aromatic hydrocarbon solvents, isoparaffin solvents and hydronaphthalene solvents respectively, which pose potential threats to human body and environment. The dearomatized solvent used in this patent is more environmentally friendly and pollution-free, and is cheap and easier to be applied in large-scale production. Summary of the invention

[0006] In view of the above problems, the object of the present invention is to provide a lithium ion positive electrode slurry in which the solvent is environmentally friendly and non-toxic dearomatized solvent oil and the binder is a rubber binder that can be dissolved in the dearomatized solvent oil.

[0007] The first aspect of the present invention is to disclose an ion battery positive electrode material slurry, including an active material, a conductive agent, a binder and a solvent;

[0008] Wherein, the solvent is environmentally friendly and non-toxic dearomatized solvent oil.

[0009] In some embodiments of the present invention, the binder is a rubber binder soluble in dearomatized solvent oil.

[0010] In some embodiments of the present invention, the dearomatized solvent oil is selected from at least one of Total Ketrul D20, Ketrul D40, Maoming Petrochemical D20, Maoming Petrochemical D60, ExxonMobil EXXSOL D30, ExxonMobil EXXSOL D60, Total Ketrul D220, Total Ketrul D110, Maoming Petrochemical D100, ExxonMobil EXXSOL D100 and Ketrul D85; preferably at least one selected from Total Ketrul D220, Total Ketrul D110, Maoming Petrochemical D100, ExxonMobil EXXSOL D100 and Ketrul D85; more preferably Total Ketrul D85.

[0011] In some embodiments of the present invention, the binder is selected from at least one of Kraton FG1924, TSRC Taipol 7131, TSRC Taipol 7126, Kraton FG1901, Kraton G1651 and Kraton G1657; preferably, it is selected from at least one of TSRC Taipol 7131, TSRC Taipol 7126, Kraton FG1924 and Kraton FG1901; further preferably, it is selected from at least one of TSRC Taipol 7131, TSRC Taipol 7126 and Kraton FG1924; and further preferably, it is Kraton FG1924.

[0012] In some embodiments of the present invention, the binder is Kraton FG1901 and Kraton G1657 in a weight ratio of (1-2): (2-1).

[0013] In some embodiments of the present invention, the binder is Kraton FG1651, Kraton G1657 and Kraton FG1924 in a weight ratio of (1-2):(1-2):(1-2).

[0014] In some embodiments of the present invention, the binder is Taipol 7126 and Kraton FG1924 in a weight ratio of (1-2): (5-10).

[0015] In some embodiments of the present invention, the binder is Taipol 7131 and Kraton FG1924 in a weight ratio of (1-2): (5-10).

[0016] In some embodiments of the present invention, the binder is Baling Petrochemical YH-688 and Kraton FG1924 in a weight ratio of (1-2): (5-10).

[0017] In some embodiments of the present invention, the active material is selected from one or more of lithium iron phosphate, lithium manganese oxide, lithium nickel cobalt manganese oxide and lithium nickel cobalt aluminum oxide.

[0018] In some embodiments of the present invention, the conductive agent is selected from one or more of conductive graphite, conductive carbon black, acetylene black, carbon nanotubes, and graphene.

[0019] In some embodiments of the present invention, the weight ratio of the binder, solvent, active material and conductive agent is (1-5): (30-40): (55-65): (1-5), preferably (1.5-3): (33-37): (59-62): (2-3).

[0020] In some embodiments of the present invention, the viscosity of the positive electrode slurry is 2000-12000 m·Pas, and preferably the viscosity of the positive electrode slurry is 5000-8000 m·Pas.

[0021] The second aspect of the present invention is to disclose a method for preparing the positive electrode material slurry of a lithium ion battery according to the first aspect, comprising the following steps:

[0022] Adding the binder and the conductive agent into the solvent and mixing them to obtain a mixed solution;

[0023] Adding the active substance to the surgical mixed solution for mixing and separation to obtain electrode slurry;

[0024] Preferably, a sieve is used for separation, and more preferably, the mesh size of the sieve is 150-180 meshes.

[0025] The third aspect of the present invention is to disclose a positive electrode for a lithium ion battery, the preparation raw materials of which include the positive electrode slurry for the lithium ion battery described in the first aspect.

[0026] The fourth aspect of the present invention is to disclose a lithium ion battery, comprising the lithium ion battery positive electrode described in the third aspect.

[0027] Beneficial effects of the present invention:

[0028] Compared with the traditional N-methylpyrrolidone and polyvinylidene fluoride system of lithium-ion positive electrode slurry, dearomatized solvent oil is a cycloalkane and chain alkane without aromatic hydrocarbons, which has good solubility properties for rubber and meets the standards of safety, health and environmental protection. The pole piece prepared by using dearomatized solvent oil and rubber as the lithium-ion battery slurry system is smooth and soft, and the peel strength of the pole piece is higher than that of the N-methylpyrrolidone and polyvinylidene fluoride system, and the battery performance is better.

[0029] In the present invention, binders and solvents with good effects are screened for different active substances. DETAILED DESCRIPTION

[0030] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0031] Unless otherwise specified, the examples and comparative examples are parallel tests with the same components, component contents, preparation steps and preparation parameters.

[0032] Example 1

[0033] This embodiment provides a positive electrode slurry for a lithium-ion battery, comprising the following raw materials in mass fractions:

[0034] Active material (lithium iron phosphate) 59%, binder (Kraton G1657) 3.0%, conductive agent (acetylene black) 3%, solvent Total Ketrul D85 35%. Slurry solid content 65wt%.

[0035] Example 2

[0036] This embodiment provides a positive electrode slurry for a lithium-ion battery, comprising the following raw materials in mass fractions:

[0037] Active material (lithium iron phosphate) 59%, binder (Kraton G1651) 3.0%, conductive agent (acetylene black) 3%, solvent is Total Ketrul D85 35%. The solid content of the slurry is 65wt%.

[0038] Example 3

[0039] This embodiment provides a positive electrode slurry for a lithium-ion battery, comprising the following raw materials in mass fractions:

[0040] Active material (lithium iron phosphate) 59%, binder (Kraton FG1924) 3%, conductive agent (acetylene black) 3%, solvent is Total Ketrul D85 35%. The solid content of the slurry is 65wt%.

[0041] Example 4

[0042] This embodiment provides a positive electrode slurry for a lithium-ion battery, comprising the following raw materials in mass fractions:

[0043] Active material (lithium iron phosphate) 59%, binder (Kraton FG1901) 3%, conductive agent (acetylene black) 3%, solvent is Total Ketrul D85 35%. The solid content of the slurry is 65wt%.

[0044] Example 5

[0045] This embodiment provides a positive electrode slurry for a lithium-ion battery, comprising the following raw materials in mass fractions:

[0046] Active material (lithium iron phosphate) 59%, binder (Kraton FG1901) 1.5%, binder (Kraton G1657) 1.5%, conductive agent (acetylene black) 3%, solvent is Total Ketrul D85 35%. The solid content of the slurry is 65wt%.

[0047] Example 6

[0048] This embodiment provides a positive electrode slurry for a lithium-ion battery, comprising the following raw materials in mass fractions:

[0049] Active material (lithium iron phosphate) 59%, binder (Kraton FG1651) 1.0%, binder (Kraton G1657) 1.0%, binder (Kraton FG1924) 1.0%, conductive agent (acetylene black) 3%, solvent is Total Ketrul D85 35%. The solid content of the slurry is 65wt%.

[0050] Example 7

[0051] This embodiment provides a positive electrode slurry for a lithium-ion battery, comprising the following raw materials in mass fractions:

[0052] Active material (lithium iron phosphate) 59%, binder (Taipol 7126) 0.5%, binder (Kraton FG1924) 2.5%, conductive agent (acetylene black) 3%, solvent Total Ketrul D85 35%. Slurry solid content 65wt%.

[0053] Example 8

[0054] This embodiment provides a positive electrode slurry for a lithium-ion battery, comprising the following raw materials in mass fractions:

[0055] Active material (lithium iron phosphate) 59%, binder (Taipol 7131) 0.5%, binder (Kraton FG1924) 2.5%, conductive agent (acetylene black) 3%, solvent Total Ketrul D85 35%. Slurry solid content 65wt%.

[0056] Example 9

[0057] This embodiment provides a positive electrode slurry for a lithium-ion battery, comprising the following raw materials in mass fractions:

[0058] Active material (lithium iron phosphate) 59%, binder (Taiwan Rubber Taipol 7131) 3.0%, conductive agent (acetylene black) 3%, solvent Total Ketrul D85 35%. Slurry solid content 65wt%.

[0059] Example 10

[0060] This embodiment provides a positive electrode slurry for a lithium-ion battery, comprising the following raw materials in mass fractions:

[0061] Active material (lithium iron phosphate) 59%, binder (Baling Petrochemical YH-688) 3.0%, conductive agent (acetylene black) 3%, solvent Total Ketrul D85 35%. Slurry solid content 65wt%.

[0062] Embodiment 11

[0063] This embodiment provides a positive electrode slurry for a lithium-ion battery, comprising the following raw materials in mass fractions:

[0064] Active material (lithium iron phosphate) 59%, binder (Baling Petrochemical YH-688) 0.5%, binder (Kraton FG1924) 2.5%, conductive agent (acetylene black) 3%, solvent Total Ketrul D85 35%. The solid content of the slurry is 65wt%.

[0065] Example 12

[0066] This embodiment provides a positive electrode slurry for a lithium-ion battery, comprising the following raw materials in mass fractions:

[0067] Active material (lithium manganate) 61%, binder (Kraton FG1924) 2.0%, conductive agent (acetylene black) 2%, solvent Total Ketrul D85 35%. Slurry solid content 70wt%.

[0068] Example 13

[0069] This embodiment provides a positive electrode slurry for a lithium-ion battery, comprising the following raw materials in mass fractions:

[0070] Active material (lithium nickel cobalt manganese oxide) 62%, binder (Kraton FG1924) 1.5%, conductive agent (acetylene black) 1.5%, solvent Total Ketrul D85 35%. Slurry solid content 75wt%.

[0071] Embodiment 14

[0072] This embodiment provides a positive electrode slurry for a lithium-ion battery, comprising the following raw materials in mass fractions:

[0073] Active material (lithium nickel cobalt aluminum oxide) 62%, binder (Kraton FG1924) 1.5%, conductive agent (acetylene black) 1.5%, solvent Total Ketrul D85 35%. Slurry solid content 75wt%

[0074] Embodiment 15

[0075] This embodiment provides a positive electrode slurry for a lithium-ion battery, comprising the following raw materials in mass fractions:

[0076] Active material (lithium iron phosphate) 59%, binder (Kraton FG1924) 3.0%, conductive agent (acetylene black) 3%, solvent Total Ketrul D30 35%. Slurry solid content 65wt%.

[0077] Example 16

[0078] This embodiment provides a positive electrode slurry for a lithium-ion battery, comprising the following raw materials in mass fractions:

[0079] Active material (lithium iron phosphate) 59%, binder (Kraton FG1924) 3.0%, conductive agent (acetylene black) 3%, solvent Total Ketrul D60 35%. The solid content of the slurry is 65wt%.

[0080] Embodiment 17

[0081] This embodiment provides a positive electrode slurry for a lithium-ion battery, comprising the following raw materials in mass fractions:

[0082] Active material (lithium iron phosphate) 59%, binder (Kraton FG1924) 3.0%, conductive agent (acetylene black) 3%, solvent Total Ketrul D100 35%. The solid content of the slurry is 65wt%.

[0083] Embodiment 18

[0084] This embodiment provides a positive electrode slurry for a lithium-ion battery, comprising the following raw materials in mass fractions:

[0085] Active material (lithium iron phosphate) 59%, binder (Kraton FG1924) 3.0%, conductive agent (acetylene black) 3%, solvent Total Ketrul D220 35%. Slurry solid content 65wt%.

[0086] Embodiment 19

[0087] This embodiment provides a positive electrode slurry for a lithium-ion battery, comprising the following raw materials in mass fractions:

[0088] Active material (lithium iron phosphate) 59%, binder (Kraton FG1924) 3.0%, conductive agent (acetylene black) 3%, solvent Maoming Petrochemical D20 35%. The solid content of the slurry is 65wt%.

[0089] Embodiment 20

[0090] This embodiment provides a positive electrode slurry for a lithium-ion battery, comprising the following raw materials in mass fractions:

[0091] Active material (lithium iron phosphate) 59%, binder (Kraton FG1924) 3.0%, conductive agent (acetylene black) 3%, solvent Maoming Petrochemical D60 35%. Slurry solid content 65wt%.

[0092] Embodiment 21

[0093] This embodiment provides a positive electrode slurry for a lithium-ion battery, comprising the following raw materials in mass fractions:

[0094] Active material (lithium iron phosphate) 59%, binder (Kraton FG1924) 3.0%, conductive agent (acetylene black) 3%, solvent Maoming Petrochemical D100 35%. Slurry solid content 65wt%.

[0095] Embodiment 22

[0096] This embodiment provides a positive electrode slurry for a lithium-ion battery, comprising the following raw materials in mass fractions:

[0097] Active material (lithium iron phosphate) 59%, binder (Kraton FG1924) 3.0%, conductive agent (acetylene black) 3%, solvent ExxonMobil EXXSOL D30 35%. Slurry solid content 65wt%.

[0098] Embodiment 23

[0099] This embodiment provides a positive electrode slurry for a lithium-ion battery, comprising the following raw materials in mass fractions:

[0100] Active material (lithium iron phosphate) 59%, binder (Kraton FG1924) 3.0%, conductive agent (acetylene black) 3%, solvent ExxonMobil EXXSOL D60 35%. Slurry solid content 65wt%.

[0101] Embodiment 24

[0102] This embodiment provides a positive electrode slurry for a lithium-ion battery, comprising the following raw materials in mass fractions:

[0103] Active material (lithium iron phosphate) 59%, binder (Kraton FG1924) 3.0%, conductive agent (acetylene black) 3%, solvent ExxonMobil EXXSOL D100 35%. Slurry solid content 65wt%.

[0104] Embodiment 25

[0105] This embodiment provides a positive electrode slurry for a lithium-ion battery, comprising the following raw materials in mass fractions:

[0106] Active material (lithium iron phosphate) 59%, binder (Kraton FG1924) 3.0%, conductive agent (acetylene black) 3%, solvent ExxonMobil EXXSOL D130 35%. Slurry solid content 65wt%.

[0107] Embodiment 26

[0108] 1 Take the lithium ion battery positive electrode slurry raw materials of Examples 1-25 to prepare lithium ion battery positive electrode slurry:

[0109] Dispersing a binder and a conductive agent in a solvent in sequence and mixing them to obtain a mixed solution;

[0110] The active material is added into the mixed solution for mixing, and then separated by a sieve with a mesh size of 150-180 to obtain a positive electrode slurry for a lithium-ion battery.

[0111] 2. Take the obtained lithium ion battery positive electrode slurry to prepare the lithium ion battery positive electrode:

[0112] The positive electrode slurry of the lithium-ion battery is evenly coated on the surface of the current collector (aluminum foil), and then dried. The dried pole piece is rolled and cut to obtain the positive electrode (pole piece) of the lithium-ion battery.

[0113] 3. Take the obtained positive electrode of the ion battery and the negative electrode of the lithium ion battery to prepare the lithium ion battery:

[0114] The positive electrode and the negative electrode of the lithium-ion battery are wound into a battery cell, and the battery cell is placed in a steel shell to obtain a lithium-ion battery.

[0115] The negative electrode of the lithium-ion battery is prepared by the following method:

[0116] The negative electrode of the lithium-ion battery is prepared by coating the negative electrode material of the lithium-ion battery on a copper foil. The negative electrode material of the lithium-ion battery includes the following raw materials by mass fraction: 95.4% of negative electrode graphite, 1% of acetylene black, 1.5% of carboxymethyl cellulose (CMC) and 2.1% of styrene-butadiene rubber (SBR).

[0117] Comparative Example 1

[0118] This comparative example provides a lithium-ion battery positive electrode slurry, comprising the following raw materials by mass fraction:

[0119] Active material (lithium iron phosphate) 59%, binder (PVDF) 3%, conductive agent (acetylene black) 3%, solvent (NMP) 35%. Slurry solid content 65wt%.

[0120] Comparative Example 2

[0121] This comparative example provides a lithium-ion battery positive electrode slurry, comprising the following raw materials by mass fraction:

[0122] Active material (lithium iron phosphate) 59%, binder (PVDF) 3%, conductive agent (acetylene black) 3%, solvent Total Ketrul D85 35%. Slurry solid content 65wt%.

[0123] Comparative Example 3

[0124] This comparative example provides a lithium-ion battery positive electrode slurry, comprising the following raw materials by mass fraction:

[0125] Active material (lithium iron phosphate) 59%, Lanxess Kraton G1657 3%, conductive agent (acetylene black) 3%, solvent (NMP) 35%. Slurry solid content 65wt%.

[0126] Comparative Example 4

[0127] This embodiment provides a positive electrode slurry for a lithium-ion battery, comprising the following raw materials in mass fractions:

[0128] Active material (lithium manganate) 61%, binder (PVDF) 2.0%, conductive agent (acetylene black) 2%, solvent (NMP) 35%. Slurry solid content 70wt%.

[0129] Comparative Example 5

[0130] This embodiment provides a positive electrode slurry for a lithium-ion battery, comprising the following raw materials in mass fractions:

[0131] Active material (lithium nickel cobalt manganese oxide) 62%, binder (PVDF) 1.5%, conductive agent (acetylene black) 1.5%, solvent (NMP) 35%. Slurry solid content 75wt%.

[0132] Comparative Example 6

[0133] This embodiment provides a positive electrode slurry for a lithium-ion battery, comprising the following raw materials in mass fractions:

[0134] Active material (lithium nickel cobalt aluminum oxide) 62%, binder (PVDF) 1.5%, conductive agent (acetylene black) 1.5%, solvent (NMP) 35%. Slurry solid content 75wt%.

[0135] In order to verify the technical effects of the lithium ion battery positive electrode and the lithium ion battery obtained by the lithium ion battery positive electrode slurry of the above embodiments and comparative examples, the following experimental examples are specially designed.

[0136] Experimental example

[0137] The lithium ion battery positive electrodes obtained from the lithium ion battery positive electrode slurries of Examples 1-25 and Comparative Examples 1-6 were tested for peel strength.

[0138] Test steps: According to the method standard GB / T 2792 "180° peel strength test method for pressure-sensitive adhesive tapes"

[0139] Principle: The sample is clamped between the two chucks of the fixture. The two chucks move relative to each other. The force sensor on the dynamic chuck and the displacement sensor built into the machine collect the force and displacement changes in the test, thereby calculating the tensile, peeling, deformation, tearing and other mechanical properties of the sample.

[0140] The specific results are shown in Table 1.

[0141] Table 1 Peel strength of positive electrode of lithium-ion battery

[0142]

[0143]

[0144]

[0145] Note: In Comparative Examples 2 and 3, the binder and the solvent are not miscible.

[0146] The lithium-ion batteries obtained from the lithium-ion battery positive electrode slurries of Examples 1-25 and Comparative Examples 1-6 were subjected to charge and discharge tests.

[0147] The test conditions are as follows: the lithium ion batteries provided in Examples 1-11, 15-25 and Comparative Example 1 were subjected to charge and discharge tests: constant current and constant voltage charging: cut-off voltage 3.65V, charging current 800mA, cut-off current 80mA, ambient temperature: 25°C; constant current discharge: cut-off voltage 2.5V, discharge current 800mA, ambient temperature 25°C; Examples 12-14 and Comparative Examples 4-6: constant current and constant voltage charging: cut-off voltage 4.2V, charging current 1250mA, cut-off current 125mA, ambient temperature: 25°C; constant current discharge: cut-off voltage 3.0V, discharge current 1250mA, ambient temperature 25°C. The test results are shown in Table 2.

[0148] The test results are shown in Table 2.

[0149] Table 2 Lithium-ion battery charge and discharge test

[0150]

[0151]

[0152] Note: In Comparative Examples 2 and 3, the binder and the solvent are not miscible.

[0153] The results show that in the embodiment with 59% active material (lithium iron phosphate), Kraton FG1924 is the best, TSRC Taipol 7131 and 7126 are better, Kraton FG1901 is medium, and Kraton G1651 and G1657 are worse. In the present invention, Total Ketrul D85 is most similar to NMP among the solvents, and is most suitable for actual production in pulping and coating, followed by Total Ketrul D220, Total Ketrul D100, Maoming Petrochemical D100, and ExxonMobil EXXSOL D100. During the coating process, the baking power of the oven needs to be increased to dry the pole piece. Finally, Total Ketrul D30, Ketrul D46, Maoming Petrochemical D20, Maoming Petrochemical D60, ExxonMobil EXXSOL D30, and ExxonMobil EXXSOL D60 are very volatile and can easily cause pole piece cracking during the coating process.

[0154] The examples with 61% active material (lithium manganese oxide), 62% active material (lithium cobalt manganese oxide), and 62% active material (lithium nickel cobalt aluminum oxide) showed similar results to the example with 59% active material (lithium iron phosphate).

[0155] The preferred specific implementation modes and embodiments of the present invention are described in detail above, but the present invention is not limited to the above implementation modes and embodiments, and various changes can be made within the knowledge scope of those skilled in the art without departing from the concept of the present invention.

Claims

1. A lithium-ion battery positive electrode material slurry, characterized in that: Including active materials, conductive agents, binders and solvents; Wherein, the solvent is environmentally friendly and non-toxic dearomatized solvent oil; the binder is a rubber binder that can be dissolved in dearomatized solvent oil; The dearomatized solvent oil is selected from at least one of Total Ketrul D30, Ketrul D40, Maoming Petrochemical D20, Maoming Petrochemical D60, ExxonMobil EXXSOL D30, ExxonMobil EXXSOL D60, Total Ketrul D220, Total Ketrul D100, Maoming Petrochemical D100, ExxonMobil EXXSOL D100 and Ketrul D85; The adhesive is selected from at least one of TSRC Taipol 7131, TSRC Taipol 7126, Kraton FG1924 and Kraton FG1901.

2. The positive electrode material slurry for lithium-ion batteries according to claim 1, characterized in that: The dearomatized solvent oil is selected from at least one of Total Ketrul D220, Total Ketrul D100, Maoming Petrochemical D100, ExxonMobil EXXSOL D100 and Ketrul D85.

3. The positive electrode material slurry for lithium-ion batteries according to claim 1, characterized in that: The dearomatized solvent oil is Total Ketrul D85.

4. The positive electrode material slurry for lithium-ion batteries according to any one of claims 1 to 3, characterized in that: The adhesive is selected from at least one of TSRC Taipol 7131, TSRC Taipol 7126 and Kraton FG1924.

5. The positive electrode material slurry for lithium-ion batteries according to any one of claims 1 to 3, characterized in that: The binder is Kraton FG1924.

6. The positive electrode material slurry for lithium-ion batteries according to any one of claims 1 to 3, characterized in that: The active material is selected from one or more of lithium iron phosphate, lithium manganate, lithium nickel cobalt manganate and lithium nickel cobalt aluminum oxide; And / or, the conductive agent is selected from one or more of conductive graphite, conductive carbon black, acetylene black, carbon nanotubes, and graphene.

7. The positive electrode material slurry for lithium-ion batteries according to any one of claims 1 to 3, characterized in that: The weight ratio of the binder, solvent, active material and conductive agent is (1-5): (30-40): (55-65): (1-5).

8. The positive electrode material slurry for lithium-ion batteries according to any one of claims 1 to 3, characterized in that: The weight ratio of the binder, solvent, active material and conductive agent is (1.5-3): (33-37): (59-62): (2-3).

9. The positive electrode material slurry for lithium-ion batteries according to any one of claims 1 to 3, characterized in that: The viscosity of the positive electrode material slurry is 2000-12000 m•Pas.

10. The positive electrode material slurry for lithium-ion batteries according to any one of claims 1 to 3, characterized in that: The viscosity of the positive electrode material slurry is 5000-8000 m•Pas.

11. A method for preparing a lithium-ion battery positive electrode material slurry according to any one of claims 1 to 10, characterized in that: The following steps are involved: Adding the binder and the conductive agent into the solvent and mixing them to obtain a mixed solution; The active material is added to the mixed solution for mixing and separation to obtain electrode slurry.

12. The method for preparing a positive electrode material slurry for a lithium-ion battery according to claim 11, characterized in that: A screen is used for separation.

13. The method for preparing a positive electrode material slurry for a lithium-ion battery according to claim 12, characterized in that: The mesh number of the sieve is 150-180 meshes.

14. A positive electrode for a lithium ion battery, characterized in that: The preparation raw materials include the positive electrode material slurry of the lithium ion battery according to any one of claims 1-10.

15. A lithium ion battery, characterized in that: Includes the lithium ion battery positive electrode as described in claim 14.

Citation Information

Patent Citations

  • Method of preparing cathode containing iron disulfide for a lithium cell

    CN102037591A

  • Preparation method of positive pole piece of lithium-ferrous disulfide cell

    CN102779973A

  • Lithium-rich manganese-based solid-state battery electrode and secondary battery

    CN111129429A

  • Positive active material and preparation method thereof, battery positive electrode sheet and lithium battery

    CN111146438A

  • Electrode for batteries, battery comprising the electrode, and method for producing the battery

    US20120156571A1